2021
DOI: 10.18203/2394-6040.ijcmph20210216
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of structured teaching programme regarding reproductive health on knowledge among adolescent girls in selected school of rural area

Abstract: Background: Reproductive health is a crucial part of general health and central features of human development. WHO reported that nearly one-third of all healthy life lost among adolescent girls because of reproductive health problems. 250 million new cases of STD occur worldwide each year with a high rate in 16-19 years age group.Methods: A quantitative study was carried out in 80 adolescent girls and the non-probability purposive sampling technique was used for the selection of the subjects and the school. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…31,32 The e-modules developed to address Adolescent Reproductive Health have been found to be effective in creating awareness among students of upper primary classes in Haryana. The results are in conjunction with studies of Lavanya S, 33 Phulambrikar RM, 34 Calabrese S, 24 Roberto AJ et al 20 and Singh S et al, 35 who reported the effectiveness of digital interventions to address reproductive and sexual health in classrooms. However, the findings of the study are antagonistic to the studies by Calise TV et al 36 and Gustina E & Wibowo M 37 who reported no change in knowledge regarding reproductive health post-intervention.…”
Section: Discussionsupporting
confidence: 76%
“…31,32 The e-modules developed to address Adolescent Reproductive Health have been found to be effective in creating awareness among students of upper primary classes in Haryana. The results are in conjunction with studies of Lavanya S, 33 Phulambrikar RM, 34 Calabrese S, 24 Roberto AJ et al 20 and Singh S et al, 35 who reported the effectiveness of digital interventions to address reproductive and sexual health in classrooms. However, the findings of the study are antagonistic to the studies by Calise TV et al 36 and Gustina E & Wibowo M 37 who reported no change in knowledge regarding reproductive health post-intervention.…”
Section: Discussionsupporting
confidence: 76%